A Study on Hypertension Among Population Living Underneath Suteti and Its Related Factors Jakarta 2009 - Corrie Wawolumaya (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: Hypertension is one of the degenerative diseases which killed about 7,2 mill people, about 13 % of the total death worldly. In Indonesia the disease has become more popular, It was reported that Indonesia had got a quite high prevalence of hypertension , among male 24,9%, female 23,6% , elderly 33,3 % , SUTETI 500 kV is the Extra High Electrical Energy Transmission lines transferring the energy from the Electrical Power Installation to the consumers via the connection of Power Relay station. The SUTETI electromagnetic exposure many times has been connected with diseases and mental emotional disorders used to be experienced by patients with hypertension such as head ache, dizziness, easily get angry, heavy neck as well as stroke. These health disturbances have been considered by many people as SUTETI’s negative health impact among people living underneath. Most of the times were used by public as the major reasons against the installation of SUTETI wire network.Method: The aim of study is to identify the relation between SUTETI exposure and hypertension, and its related factors among population living underneath. Another objective of study is to identify the relation between mental emotional factors and hypertension. The population was people living underneath SUTETI 0-100 ms right and left away from the towers. The number of samples collected was about 2000 people with the calculated sample size 753 and were stratified into three zones, zone 1 , 0-30 ms right and left from the tower, zone 2 , 30-70 ms and zone 3 ,70-100 ms. The independent variables were sociodemographic factors i.e., age, sex, education, income , length of stay at home, duration of stay at the location, besides smoking habit, annoyance, satisfaction, electrical field dose , magnetic field dose and zone . Blood chemistry examined were cholesterol and nutritional status besides melatonin, mental emotional and sleeping disorders.Result and conclusions: Study results reported that the highest outside the house measurements of the electric field was in zone 1 , 3,2 kV/m and magnetic field was 6,7 X 10-² mT , both were still lower than the National Standard of SUTETI in Indonesia – SNI 2003 , 5 kV/m and 0,1 mT. The prevalence of hypertension based on zone were significant , zone 1, 14,14%, zone 2 , 11,31% and zone 3, 5,66 % ( p = 0,004) The logistic regression function analysis identified two determinants, duration of stay ( p = 0,044 ) ; OR 3,85 (95 %CI :1,04 – 14, 12) ; income ( p = 0,019 , OR 15, 891 ( 95% CI: 1,578 – 169,97). People living > 30 years under the SUTETI towers (0 – 100ms ) will be risky 3,85 times to get hypertension than people living less than 30 years. Also people with less income had the risk 16 times to get hypertension compared to middle income. The results did not reveal any specific evidence of association between the electromagnetic exposure and hypertension. The logistic regression function also did not identify any association between mental emotional disorders and sleeping disorders towards hypertension.Keywords: hypertension, SUTETI, mental emotional disorders